Implementation of Restorative Justice Principles in Resolving Juvenile Crimes in School Environments: A Case Study in Three Middle Schools in Central Lombok - Imam Alfurqan; M. Sofian Assaori; Suntarajaya Kwangtama Tekayadi; Khalid Prawiranegara (Jurnal Multidisiplin Sahombu, 2026)
This study aims to analyze the implementation of restorative justice in resolving juvenile delinquency cases within school settings, particularly in three public junior secondary schools in Central Lombok, Indonesia. The research employs a qualitative approach with a multiple case study design, involving school counselors, principals, student offenders, victims, and parents. Data were collected through in-depth interviews, observations, and document analysis, and analyzed interactively through data reduction, data display, and conclusion drawing. The findings indicated that all cases were resolved through internal school mechanisms with a relatively low rate of recurrence. The implementation of restorative justice follows systematic stages, including case identification, information gathering, restorative dialogue, agreement formulation, and monitoring. A key finding reveals a hybrid model integrating formal institutional procedures with contextual socio-cultural practices. The success of implementation is strongly influenced by the role of school counselors as primary mediators and the active involvement of parents. This study confirms that restorative justice is an effective, adaptive, and relevant approach in fostering educational conflict resolution within schools. The findings contribute both theoretically and practically to the development of more humane and sustainable approaches to managing student misconduct